2019
DOI: 10.3390/nano9020270
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Antioxidant and Antimicrobial Properties of Electrospun Poly(ε-caprolactone) Films Containing a Solid Dispersion of Sage (Salvia officinalis L.) Extract

Abstract: In this study, novel active films made of poly(ε-caprolactone) (PCL) containing a solid dispersion of sage extract (SE) were developed by means of the electrospinning technique and subsequent annealing treatment. Initially, the antioxidant and antimicrobial potential of SE was confirmed. Thereafter, the effect of SE incorporation at different loading contents (5%, 10%, and 20%) on the physicochemical and functional properties of the films was evaluated. The films were characterized in terms of morphology, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 53 publications
14
44
0
Order By: Relevance
“…Despite the fact that PCL and PVP are polymers with no antimicrobial properties, our results showed that pure PCL in the form of fibers show slight antimicrobial activity for S. aureus and E. coli ( Figure S5); similar results were previously reported by Lagarón and his group [96]. Some evidence can be found that PCL and PVP are not ignored by bacterial cells and the growth is altered, after certain time bacteria recover their viability.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Despite the fact that PCL and PVP are polymers with no antimicrobial properties, our results showed that pure PCL in the form of fibers show slight antimicrobial activity for S. aureus and E. coli ( Figure S5); similar results were previously reported by Lagarón and his group [96]. Some evidence can be found that PCL and PVP are not ignored by bacterial cells and the growth is altered, after certain time bacteria recover their viability.…”
Section: Discussionsupporting
confidence: 89%
“…Ag-Si/Al 2 O 3 possesses antiseptic qualities and biocompatibility for biological tissues in animal experiments [41]. They also showed a bactericidal effect against Escherichia coli [96] and excellent bactericidal and fungicidal properties [105,106]. As mentioned in the results, all sorbents evaluated in this work present an increase in antimicrobial potency over time, being the most evident effect for P. aeruginosa.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In both techniques, an electrical potential is applied between a droplet of a matrix solution held at the end of a capillary tube and grounded target and when the applied electric field overcomes the surface tension of the droplet, a charged jet of solution is ejected (López de Dicastillo et al, ). Several works have already shown the effectiveness of encapsulation of active compounds, such as vanillin, curcumin, natural extracts, and essential oils, into different electrospun matrixes such as polymers and proteins (Arrieta, López de Dicastillo, Garrido, Roa, & Galotto., ; Kayaci & Uyar, ; Pérez‐Masiá et al, ; Rieger & Schiffman, ; Salevic, Prieto, Cabedo, Nedovic, & Lagaron, ; Torkamani, Syahariza, Norziah, Wan, & Juliano, ; Wang et al, ). Thus, this work presents the selection of a powerful extract of maqui fruit (MQE) based on its polyphenolic, antioxidant, antimicrobial, and anti‐tyrosinase properties to be further successfully encapsulated into electrospun hydroxypropyl‐β‐cyclodextrin (HPβCD) capsules.…”
Section: Introductionmentioning
confidence: 99%